A multidisciplinary approach to the diagnosis of antisynthetase syndrome - Wells, Matthew; Alawi, Sughra; Thin, Kyaing Yi Mon; Gunawardena, Harsha; Brown, Adrian R.; Edey, Anthony; Pauling, John D.; Barratt, Shaney L.; Adamali, Huzaifa I. (Frontiers in Medicine, 2022)
Antisynthetase syndrome is a subtype of idiopathic inflammatory myopathy, strongly associated with the presence of interstitial lung disease. Diagnosis is made by identifying myositis-specific antibodies directed against aminoacyl tRNA synthetase, and relevant clinical and radiologic features. Given the multisystem nature of the disease, diagnosis requires the careful synthesis of subtle clinical and radiological features with the interpretation of specialised autoimmune serological testing. This is provided in a multidisciplinary environment with input from rheumatologists, respiratory physicians and radiologists. Differentiation from other idiopathic interstitial lung diseases is key; treatment and prognosis differs between patients with antisynthetase syndrome and idiopathic interstitial lung disease. In this review article, we look at the role of the multidisciplinary team and its individual members in the initial diagnosis of antisynthetase syndrome, including the role of physicians, radiologists and the wider team.